Dual training system as a corporate social responsibility modality for entrepreneurial community development - Perez, John Erinorio M.; Cardenas, Virginia R.; Quimbo, Maria Ana T. (2015)
The Dual Training System (DTS) is an educational system that encourages partnership with the private sector as guided and protected by the Philippines Law R.A. 7686. MAong the objectives of the DTS Law is to strengthen training cooperation between business establishments and educational institutions. In the DTS model, implementers in the educational institution facilitate DTS, while partner establishments work as cooperating companies. The latter implements DTS as their companies' Corporate Social Responsibility (CSR).
This study explored the roles of the cooperating companies and the institution of Dualtech Center in implementing the DTS being a CSR modality. This helps students become potential members of the entrepreneurial community. Using the prescribed curriculum, the respondent companies were asked to evaluate their role performance in conducting DTS. Their responses were measured by getting the weighted mean of their performance ratings.
The weighted mean derived for the cooperating companies was 3.00. The implementers rated their performance at a weighted mean of 3.70. The results indicated that the cooperating companies were doing the supporting roles in the DTS implementation.
in conclusion, both the implementers and cooperating companies perceived that they were performing their respective roles well in the implementation of DTS.
Keywords: Social responsibility of business; Community development